Psychometric properties of Malay neuropsychiatry unit cognitive assessment tool among Alzheimer's disease patients in comparison to Malay Montreal Cognitive Assessment. (29th November 2015) - Thong, Kai Shin; Chee, Kok Yoon; Ng, Chong Guan; Walterfang, Mark; Velakoulis, Dennis
Abstract: This study aims to establish psychometric properties of the Malay Neuropsychiatry Unit Cognitive Assessment Tool (Malay NuCOG) in Alzheimer's disease. NuCOG was translated to Malay language and compared with Montreal Cognitive Assessment Tool on 80 individuals. The Malay NuCOG showed good internal consistency and reliability (Cronbach's alpha = 0.895). It demonstrated 100% sensitivity and 87.5% specificity at the cutoff score of 78.50/100. The Malay NuCOG is a valid and reliable cognitive instrument that is sensitive and specific for the detection of dementia and has clinical advantages in its ability to examine individual cognitive domains.